2018
DOI: 10.1002/jcb.26752
|View full text |Cite
|
Sign up to set email alerts
|

The prolactin‐release inhibitor paeoniflorin suppresses proliferation and induces apoptosis in prolactinoma cells via the mitochondria‐dependent pathway

Abstract: Prolactinomas are the most prevalent functional pituitary adenomas that cause chronic pathological hyperprolactinemia. Prolactin is known to promote cell growth and inhibit apoptosis in cells. Paeoniflorin is the principal component of radix Paeoniae alba (the main ingredient in some traditional herbal formulas clinically used for hyperprolactinemia-associated disorders). Recent findings from intensive studies have suggested that paeoniflorin regulates cell proliferation and apoptosis in many cell lines. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…31 It is believed that the upregulation of pro-apoptosis factor Bax and the downregulation of anti-apoptosis factor Bcl-2 lead to cell apoptosis. As shown in some research, PF increases the Bax-to-Bcl-2 ratio in HepG2, SMMC-7721, 59 HeLa, 27 RT4, 31 MMQ, 60 HOS, and Saos-2 cells. 25 Mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway.…”
Section: Apoptosissupporting
confidence: 52%
See 2 more Smart Citations
“…31 It is believed that the upregulation of pro-apoptosis factor Bax and the downregulation of anti-apoptosis factor Bcl-2 lead to cell apoptosis. As shown in some research, PF increases the Bax-to-Bcl-2 ratio in HepG2, SMMC-7721, 59 HeLa, 27 RT4, 31 MMQ, 60 HOS, and Saos-2 cells. 25 Mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway.…”
Section: Apoptosissupporting
confidence: 52%
“…33 PF was also reported to upregulate both cleave caspase-3 and -9 in prolactinoma MMQ cells in a concentration-dependent manner. 60 Activation of caspase-3 and -9 was also detected in PF-treated BXPC-3, 29 SKO-007, 35 and HT29 cells. 57 Yang et al found that PF increased the activities of caspase-3, caspase-8, and caspase-9, thus inducing apoptosis in bladder carcinoma RT4 cells.…”
Section: The Anticancer Mechanisms Of Pfmentioning
confidence: 94%
See 1 more Smart Citation
“…Melatonin is able to selectively block the production of VEGF and ROS and even reverse angiogenesis, which can result in reduced ROS and a lack of tumor nutrition in the TME 193 . Paeoniflorin increased the expression of cleaved caspase‐9, caspase‐3, and Bax and inhibited the expression of Bcl‐2 in MMQ cells and GH3 cells, thereby inducing mitochondria‐mediated apoptosis, which ultimately manifested as a decrease in cell viability and inhibited proliferation 194,195 …”
Section: Targeting Oxidative Stress To Treat Pitnetsmentioning
confidence: 99%
“…Indeed, elevated mitophagy and mitochondrial dysfunction may favour resistance to chemotherapy in the pituitary GH3 cell line ( 131 ). Conversely, activation of mitochondria-mediated apoptosis has been proposed, which might favour novel therapy drugs ( 132 134 ). Although this evidence validates the significant roles of mitochondrial functions and adaptability in pituitary tumorigenesis, their molecular mechanisms still need to be clarified.…”
Section: Introductionmentioning
confidence: 99%